Inhalation bioaccessibility of multi-class organic pollutants associated to atmospheric PM2.5: Correlation with PM2.5 properties and health risk assessment. (15th August 2022) - Sánchez-Piñero, Joel; Novo-Quiza, Natalia; Pernas-Castaño, Cristina; Moreda-Piñeiro, Jorge; Muniategui-Lorenzo, Soledad; López-Mahía, Purificación
Abstract: Inhalation exposure to fine particulate matter (PM2.5 ) represents a global concern due to the adverse effects in human health. In the last years, scientific community has been adopted the assessment of the PM2.5 -bound pollutant fraction that could be released (bioaccessible fraction) in simulated lung fluids (SLFs) to achieve a better understanding of PM risk assessment and toxicological studies. Thus, bioaccessibility of 49 organic pollutants, including 18 polycyclic aromatic hydrocarbons (PAHs), 12 phthalate esters (PAEs), 11 organophosphorus flame retardants (OPFRs), 6 synthetic musk compounds (SMCs) and 2 bisphenols in PM2.5 samples was evaluated. The proposed method consists of a physiologically based extraction test (PBET) by using artificial lysosomal fluid (ALF) to obtain bioaccessible fractions, followed by a vortex-assisted liquid-liquid microextraction (VALLME) and a final analysis by programmed temperature vaporization-gas chromatography-tandem mass spectrometry (PTV-GC-MS/MS). The highest inhalation bioaccessibility ratio was found for bisphenol A (BPA) with an average of 83%, followed by OPFRs, PAEs and PAHs (with average bioaccessibilities of 68%, 41% and 34%, respectively). Correlations between PM2.5 composition (major ions, trace metals, equivalent black carbon (eBC) and UV-absorbing particulate matter (UVPM)) and bioaccessibility ratios were also assessed. Principal Component Analysis (PCA) suggested that PAHs, PAES and OPFRs bioaccessibility ratios could be positively correlated with PM2.5 carbonaceous content. Furthermore, both inverse and positive correlations on PAHs, PAEs and OPFRs bioaccessibilites could be accounted for some major ions and metal (oid)s associated to PM2.5, whereas no correlations comprising considered PM2.5 major ions and metal (oid)s contents and BPA bioaccessibility was observed. In addition, health risk assessment of target PM2.5 -associated PAHs via inhalation was assessed in the study area considering both total and bioaccessible concentrations, being averaged human health risks within the safe carcinogenic and non-carcinogenic levels. Graphical abstract: Image 1 Highlights: Bisphenol A showed the highest inhalation bioaccessible ratio, accounting for 83%. A correlation between logKow and bioaccessibility was found for some compounds. Bioaccessibilities seemed to be positively correlated with PM2.5 carbon content. Human health risks for PM2.5 -bound PAHs via inhalation were within the safe range.